The Importance of Using Gestalt and Grid in Building Brands - Ricco Placido da Silva, Joao Carlos [UNESP]; Paschoarelli, Luis Carlos [UNESP]; Placido da Silva, Jose Carlos [UNESP]; Stephanidis, C (Springer, 2015)
The lack of a targeted projetual method has hindered the new professionals in developing new brands. The use of specific techniques of graphical validating enables the reduction of concordance errors in a graphic mark. This study demonstrates the importance of two techniques of visual theory that assist the development of projects in this area. Being evaluated in already existing brands on the market, which proves the most important items in this graphic development process, demonstrating because they are effective.
Keywords: Brands; Gestalt; Grid; Projetual method